ANALYSIS OF WAREHOUSE LAYOUT DESIGN PT PLN (Persero) UP3 CIPUTAT - Witji Wiyono (Sean Institute, 2023)
Warehouse is one of the important things in the electricity business. A good warehouse layout often escapes the attention of business people. Warehouse layout is very important for business continuity, because the warehouse is directly related to the electricity distribution supply chain. This study aims to analyze the warehouse layout applied to PT PLN (Persero) UP3 Ciputat. The research method used is descriptive qualitative method. The results showed that the new warehouse layout was more effective, material handling became more efficient and flexibility in material distribution increased. Arrangement of goods based on the movement of goods, namely Fast moving, slow moving and dead moving. Judging from the location strategy, the warehouse has a strategic warehouse location. The existing warehouse administration has clear and relatively effective standard operating procedures.